Nonperforming Loans in the GCC Banking System and their Macroeconomic Effects - Espinoza, Raphael (IMF Working Papers; Working Paper ;, 2010)
According to a dynamic panel estimated over 1995 - 2008 on around 80 banks in the GCC region, the NPL ratio worsens as economic growth becomes lower and interest rates and risk aversion increase. Our model implies that the cumulative effect of macroeconomic shocks over a three year horizon is indeed large. Firm-specific factors related to risk-taking and efficiency are also related to future NPLs. The paper finally investigates the feedback effect of increasing NPLs on growth using a VAR model. According to the panel VAR, there could be a strong, albeit short-lived feedback effect from losses in banks' balance sheets on economic activity, with a semi-elasticity of around 0.4.